Cytoplasmic CXCR4 expression in breast cancer: induction by nitric oxide and correlation with lymph node metastasis and poor prognosis - Yasuoka, Hironao (BioMed Central, 2008)
BACKGROUND: Lymph nodes constitute the first site of metastasis for most malignancies, and the extent of lymph node involvement is a major criterion for evaluating patient prognosis. The CXC chemokine receptor 4 (CXCR4) has been shown to play an important role in lymph node metastasis. Nitric oxide (NO) may also contribute to induction of metastatic ability in human cancers. METHODS: CXCR4 expression was analyzed in primary human breast carcinoma with long-term follow-up. The relationship between nitrotyrosine levels (a biomarker for peroxynitrate formation from NO in vivo) and lymph node status, CXCR4 immunoreactivity, and other established clinico-pathological parameters, as well as prognosis, was analyzed. Nitrite/nitrate levels and CXCR4 expressions were assessed in MDA-MB-231 and SK-BR-3 breast cancer cell lines after induction and/or inhibition of NO synthesis. RESULTS: CXCR4 staining was predominantly cytoplasmic; this was observed in 50%(56/113) of the tumors. Cytoplasmic CXCR4 expression was significantly correlated with nitrotyrosine levels and lymph node metastasis. Kaplan-Meier survival curves showed that cytoplasmic CXCR4 expression was associated with reduced disease-free and overall survival. In multivariate analysis, cytoplasmic CXCR4 expression emerged as a significant independent predictor for overall and disease-free survival. Cytoplasmic expression of functional CXCR4 in MDA-MB-231 and SK-BR-3 cells was increased by treatment with the NO donor DETA NONOate. This increase was abolished by L-NAME, an inhibitor of NOS. CONCLUSION: Our data showed a role for NO in stimulating cytoplasmic CXCR4 expression in vitro. Formation of the biomarker nitrotyrosine was also correlated with CXCR4 expression and lymph node metastasis in vivo. In addition, cytoplasmic CXCR4 expression may serve as a significant prognostic factor for long-term survival in breast cancer.